Clinical Significance of Diffusely Increased Uptake of 68Ga-FAPI in Thyroid Gland - Liu, Huipan; Yang, Xiao; Liu, Lin; Lei, Lei; Wang, Li; Chen, Yue (Frontiers in Medicine, 2021)
Purpose: To determine the clinical significance of diffuse uptake of 68Ga-FAPI in the thyroid. Methods: From January 2020 to September 2021, all subjects with diffuse thyroid uptake in 68Ga-FAPI PET/CT were investigated in our hospital, and compared with the age and sex matched control group. The 68Ga-FAPI uptake in the thyroid gland was analyzed semi-quantitatively using the maximum standardized uptake value (SUVmax), and regression analysis was used to analyze the correlation between available serum thyroid stimulating hormone (TSH) and thyroid peroxidase antibody (TPOAb). Results: Among 815 subjects, 39 subjects were found diffuse FAPI uptake in thyroid gland; 11 subjects refused further examination; a total of 28 subjects were included in the analysis, and 27 subjects were diagnosed with chronic thyroiditis (including 20 subjects with Hashimoto’s thyroiditis), 3 subjects with Grave's disease, 3 subjects with only serum TSH elevated, and 1 subject with malignant of thyroid and thyroiditis. The SUVmax of 27 subjects with thyroiditis was 5.75±5.45. No significant correlation was found between the SUVmax and the level of serum TSH (P=0.389) or TPOAb (P=0.426). Conclusion: The incidentally discovered diffusely increased 68Ga-FAPI uptake in the thyroid gland is mostly related to chronic lymphocytic (Hashimoto’s) thyroiditis. 68Ga-FAPI uptake level correlated neither with the degree of hypothyroidism nor with the titer of TPOAb. In addition, immune-related thyroiditis with immune checkpoint inhibitors may be accidentally found on 68Ga-FAPI, which may be helpful in facilitate timely intervention.